The roles of financial development and urbanization in degrading environment in Africa: Unravelling non-linear and moderating impacts - Ehigiamusoe, K.U. (Elsevier Ltd, 2022)
The detrimental effects of carbon dioxide emissions (CO2) and ecological footprint (EF) on the ecosystems, climate change and global warming necessitate the adoption of various methods to ameliorate them. An insight into the root causes of CO2 and EF is fundamental for policy decisions on environmental sustainability. Though some scholars have shown some drivers of CO2 and EF, the non-linear and moderating impacts of financial development (FIN) and urbanization (URB) in degrading the environment in Africa has not been thoroughly investigated. Consequently, the purpose of this research is to examine the non-linear roles of FIN and URB in degrading the environment with emphasis on CO2 and EF in a sample of 31 African nations. It also determines the roles of FIN and URB in moderating the environment-energy nexus It utilizes empirical techniques that accommodate cross-sectional dependency, endogeneity and heterogeneity. The main results indicate that URB has an inverted U-shaped effect on CO2 while FIN has a tenuous U-shaped impact. URB and EF have a U-shaped relationship albeit FIN has a tenuous non-linear impact on EF. Besides, URB plays a mitigating role in the connection between CO2 and energy use whereas FIN plays a detrimental role. Further analysis indicates that FIN cannot moderate the nexus between energy use and EF albeit URB does aggravates the relationship. This research underscores the roles of FIN and URB on the environment in Africa. It notes that the proxy used to measure environmental degradation matters in considering the roles of FIN and URB on environment. As a result, the environmental regulations and energy policies that ignore the roles of URB and FIN may impede the pursuit of sustainable environment and development. Â© 2022 The Authors